Global transcriptome responses including small RNAs during mixed‐species interactions with methicillin‐resistant Staphylococcus aureus and Pseudomonas aeruginosa. Issue 3 (21st November 2016) - Miller, Christine L.; Van Laar, Tricia A.; Chen, Tsute; Karna, S. L. Rajasekhar; Chen, Ping; You, Tao; Leung, Kai P.
Abstract: Pseudomonas aeruginosa and Staphylococcus aureus mixed‐species biofilm infections are more resilient to biocide attacks compared to their single‐species counterparts. Therefore, this study used an in vitro model recapitulating bacterial burdens seen in in vivo infections to investigate the interactions of P. aeruginosa and S. aureus in biofilms. RNA sequencing (RNA‐seq) was utilized to identify the entire genomic response, both open reading frames (ORFs) and small RNAs (sRNAs), of each species. Using competitive indexes, transposon mutants validated uncharacterized PA1595 of P. aeruginosa and Panton–Valentine leukocidin ORFs of S. aureus are required for competitive success. Assessing spent media on biofilm development determined that the effects of these ORFs are not solely mediated by mechanisms of secretion. Unlike PA1595, leukocidin ( lukS‐PV ) mutants of S. aureus lack a competitive advantage through contact‐mediated mechanisms demonstrated by cross‐hatch assays. RNA‐seq results suggested that during planktonic mixed‐species growth there is a robust genomic response or active combat from both pathogens until a state of equilibrium is reached during the maturation of a biofilm. In mixed‐species biofilms, P. aeruginosa differentially expressed only 0.3% of its genome, with most ORFs necessary for growth and biofilm development, whereas S. aureus modulated approximately 5% of its genome, with ORFs suggestive of a phenotype of increased virulence and metabolic quiescence. Specific expression of characterized sRNAs aligned with the genomic response to presumably coordinate the adaptive changes necessary for this homeostatic mixed‐species biofilm and sRNAs may provide viable foci for the design of future therapeutics. Abstract : Polymicrobial biofilm infections comprised of P. aeruginosa and S. aureus lead to more wound healing impairment and are more antibiotic resistant compared to biofilm infections by just one of these pathogens alone. Therefore, our work utilized custom RNA‐sequencing methods to unbiasedly capture the global transcriptome response, including small RNAs, of each species during polymicrobial growth to reveal novel interspecies interactions and foster identification of targets for future therapeutics. Our work identified novel genes facilitating the success and persistence of each species in a polymicrobial biofilm, shed light on the physiological role of numerous small RNAs, and found that small RNAs of known function parallel with the genomic response to presumably coordinate these interspecies interactions.